Flexible radiochromic dosimeters development for complex irradiation beams. Issue 1 (1st January 2022) - Tran, Johanna; Agelou, Mathieu; Amiot, Marie-Noëlle; Boissonnat, Guillaume; Dehe-Pittance, Chrystèle; Girard, Hugues; Lazaro, Delphine; Simic, Vesna; Tromson, Dominique
Abstract: In vivo dosimetry for patient radioprotection is a real challenge concerning new radiotherapy treatments. In this study we aim to develop a dosimeter based on tissue equivalent material, flexible and adaptable to the patient morphology in order to perform in vivo dosimetry for complex irradiation beams. Here, we report the evaluation in standard beams of highly flexible dosimeter composed of a silicone elastomer and containing leucomalachite green as radiochromic dye and give a first estimation of LMG-micelle hydrogel response. All results are compared to a commercially available PRESAGE® dosimeter.